Gender dimensions to the incidence of tariff liberalization - Reza C. Daniels (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper evaluates a topic in the globalization and poverty debate that is often difficult to measure, namely the transmission of price changes associated with tariff liberalization to households. Furthermore, it raises the question of whether there are discernible differences between male- and female-headed households that affect this consumption-trade link. It is a partial analysis as a consequence, but one that demonstrates the importance of such a focus for continued research and policy development surrounding the impacts of globalization. Specifically, the paper evaluates how tariff changes impacted male- and female-headed households in South Africa over the discrete periods 1995, 2000, and 2004. The analysis of consumption trends by sex of household head shows statistically significant differences which confirm that resources are managed differently between the sexes, and these are transmitted through to the tariff incidence analysis. On the whole, it was found that: (1) male-headed households almost always bear a greater share of the tariff incidence compared to female-headed; (2) both male- and female-headed households – across all expenditure quantiles other than the most wealthy – bear a greater share of the tariff burden compared to their share of total expenditure; and (3) changes to the incidence over 1995, 2000, and 2004 between the sexes mimicked the trends for the population as a whole, but showed crucial differences at the bottom end of the expenditure distribution. This suggests that the sex of the household head matters, and must be considered in addition to other household identifying factors (e.g. socio-economic status) when evaluating the impacts of tariff liberalization. – trade ; poverty ; gender ; South Africa
Keywords: F14; J16; 330; Außenhandelsliberalisierung; Zoll; Verbraucherausgaben; Armut; Geschlecht; Südafrika